A History of Danish Cinema - Thomson, C. Claire; Thorsen, Isak; Chow, Pei-Sze (Edinburgh University Press, 2022)
The first English-language book to cover Danish cinema from the 1890s to the present dayContextualises the work of renowned filmmakers including Carl Th. Dreyer, Lars von Trier, Thomas Vinterberg, Susanne BierDiscusses national genres and traditions, including popular comedies, heritage film, children's film, porn, documentary and immigrant filmmakersExamines a range of film institutions and policies, including production companies, state support, talent development, regional film funds and international collaborationsThis wide-ranging collection places well-known auteurs such as Carl Th. Dreyer, Lars von Trier and Susanne Bier in their cultural context, and introduces a number of genres and themes that are less familiar to international audiences, including film stars of the silent era, children's film, folk comedies, porn film, trends in documentary and Greenlandic cinema. With twenty-two chapters, all of them specially commissioned for this volume, A History of Danish Cinema explores the role of screen representations and film policy in shaping Denmark's cultural identity, but also emphasises just how internationally mobile Danish films and filmmakers have always been - showcasing this small nation's extraordinary contribution to world cinema.
Keywords: Geschichte; Film, Media & Cultural Studies; PERFORMING ARTS / Film & Video / Direction & Production; Motion pictures -- Denmark -- History; Film; Kino; Dänemark; Aufsatzsammlung